A double-blind, randomised, placebo-controlled, dose-finding trial of the novel tuberculosis vaccine AERAS-402, an adenovirus-vectored fusion protein, in healthy, BCG-vaccinated infants. Issue 25 (9th June 2015) - Tameris, M.; Hokey, D.A.; Nduba, V.; Sacarlal, J.; Laher, F.; Kiringa, G.; Gondo, K.; Lazarus, E.M.; Gray, G.E.; Nachman, S.; Mahomed, H.; Downing, K.; et al.
Abstract: Background: Several novel tuberculosis vaccines are currently in clinical trials, including AERAS-402, an adenovector encoding a fusion protein of Mycobacterium tuberculosis antigens 85A, 85B, and TB10.4. A multicentred trial of AERAS-402 safety and immunogenicity in healthy infants was conducted in three countries in sub-Saharan Africa, using an adaptive design. Methods: In a double-blind, randomised, placebo-controlled, dose-finding trial, we enrolled BCG-vaccinated, HIV-uninfected infants aged 16–26 weeks. Infants in the safety/dose-finding phase received two doses of AERAS-402 across three dose levels, or placebo, intramuscularly on days 0 and 28. Infants in the expanded safety phase received three doses of the highest dose level, with the 3rd dose at day 280. Follow up for safety and immunogenicity was for up to two years. Results: We enrolled 206 infants (52 placebo and 154 AERAS-402 recipients) into the dose-finding phase and 281 (141 placebo and 140 AERAS-402 recipients) into the expanded safety phase. Safety data were acceptable across all dose levels. No vaccine-related deaths were recorded. A single serious adverse event of tachypnoea was deemed related to study vaccine. Antibodies directed largely against Ag85A and Ag85B were detected. Low magnitude CD4+ and CD8+ polyfunctional T cell responses were observed at all dose levels. The addition of a third dose of AERAS-402 at the highest dose level did not increase frequency or magnitude of antibody or CD8+ T cell responses. Conclusions: AERAS-402 has an acceptable safety profile in infants and was well tolerated at all dose levels. Response rate was lower than previously seen in BCG vaccinated adults, and frequency and magnitude of antigen-specific T cells were not increased by a third dose of vaccine.